Integrasi Nilai-Nilai Islam dan Kearifan Lokal - Salamah, Umi (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to analyze the integration of Islamic values and local wisdom as an effort to build interreligious harmony in public universities. The research method used is a literature review through a descriptive analytical approach to various studies related to the themes of pluralism, multicultural education, and local wisdom. The object of this research is the concept of integrating religious values and local culture in the context of higher education. The results showed that the application of tolerant Islamic values combined with local wisdom tends to have a more harmonious and inclusive academic atmosphere. This integration has proven effective in creating a space for interreligious dialogue, preventing potential conflicts, and strengthening the spirit of togetherness. In conclusion, the integration of religious values and local culture has great potential in strengthening harmony on campus. This study recommends strengthening harmony-based education policies by including religious values and local wisdom in the curriculum and student activities